The BSSO Foundry: A community of practice for ontologies in the behavioural and social sciences [version 1; peer review: 1 approved, 2 approved with reservations] - Paulina Schenk; William R. Hogan; Robert West; Björn Gehrke; Janna Hastings; Marta M. Marques; Bruce Chorpita; Harriet M. Baird; Lisa Zhang; Thomas L. Webb; Geert Crombez; Susan Michie; et al. (Wellcome Open Research)
There has been a rapid expansion in the quantity and complexity of data, information and knowledge created in the behavioural and social sciences, yet the field is not advancing understanding, practice or policy to the extent that the insights warrant. One challenge is that research often progresses in disciplinary silos and is reported using inconsistent and ambiguous terminology. This makes it difficult to integrate and aggregate findings to produce cumulative bodies of knowledge that can be translated to applied settings. Ontologies can address these challenges; their development and use have the potential to accelerate the behavioural and social sciences. Ontologies can facilitate communication through precise specification and dissemination of terms, and enable efficient data integration, sharing, comparison and analysis. The widespread use of ontologies in the biomedical and biological sciences has led to multiple successes. It is time now for the behavioural and social sciences to follow that lead. In recent years, a number of ontologies have been developed within the behavioural and social sciences; however, efforts have tended to be isolated, with limited resources to support developers and those who work (or would like to work) with and use ontologies. There is a need for coordination and exchange to reduce duplication of work and leverage the value of a community to support the interoperability of these ontologies (linking of entities across domains and datasets). We have therefore initiated the Behavioural and Social Sciences Ontology (BSSO) Foundry, a community of practice and online repository for the development, adoption and use of ontologies in the behavioural and social sciences. The BSSO Foundry aligns with and builds upon the model provided by the Open Biological and Biomedical Ontology Foundry. We describe this new initiative and how to join and contribute to the community of interoperable ontologies for the behavioural and social sciences.